Efficient Transfer Hydrogenation of Nitro Compounds to Amines Enabled by Mesoporous N-Stabilized Co-Zn/C - Xu, Yufei; Long, Jingxuan; Zhao, Wenfeng; Li, Hu; Yang, Song (Frontiers in Chemistry, 2019)
N-doped metal materials with enhanced stability and abundant porosity have attracted tremendous attention in catalytic reactions. Herein, a simple solvothermal approach was demonstrated to significantly enlarge the pore dimension of conventional microporous zeolitic imidazolate framework (ZIF) incorporated with two kinds of central metals (Co, Zn), while maintaining the original ZIF crystal morphology. Upon further pyrolysis, the resulting mesoporous Co-Zn/N-C material could possess the highly dispersed metal particle on the N-doped carbon, with satisfactory pore volume and surface area. The partial vaporization of Zn and the stabilizing effect of N, illustrated by XRD, HRTEM, HAADF-STEM with mapping, SEM, Raman Spectrum, BET, and TGA, were able to remarkably increase the accessibility of substrate toward active sites and prevent the aggregation of metal particles, respectively. Under mild reaction conditions, the N-stabilized Co-Zn/N-C exhibited good activity and selectivity in transfer hydrogenation of various nitro compounds to corresponding amines, where a synergistic role among Co, Zn, and N was responsible for its superior performance to other tested catalysts. In addition, the N-doped non-noble metal/carbon heterogeneous catalyst was fairly stable and could be reused several times without obvious deactivation.